Online Prediction with Variable Horizon for Vehicle's Future Driving-Cycle. (May 2017) - He, Hongwen; Cao, Jianfei; Peng, Jiankun
Abstract: With traditional driving cycle predictive model, the state point in vehicle-acceleration projection plane couldn't cover the real driving state completely. And date-missing caused by this lead to interruption of the prediction process. So in this paper, a real-time prediction model with variable horizon is proposed to solve the problem. Real driving data is used to reconstruct the driving cycle and the accuracy of the real time prediction model could be estimated based on historical information. By using principal component analysis and cluster analysis, an online prediction model with variable horizon based on Marco Chain is established. The correctness of this method is verified by experiment of Hardware-in-loop simulation. And the result shows that the accuracy of variable time prediction model is 8.203km/h, which has been improved by 20% comparing with fixed time prediction model.